Pyrazolone derivatives as corrosion inhibitors of copper in sulfuric acid solution - Rehab E. Azooz; Salah M. Abd El-Haleem; Ahmed Diab (Journal of Electrochemical Science and Engineering)
This study examines the corrosion inhibition of copper in aerated H2SO4 solution using 5-methyl, 5-phenyl, and 5-methyl-2-phenyl derivatives of 2,4-dihydro-3H-pyrazol-3-one (Py) through electrochemical techniques, gravimetric method, SEM, DFT and Monte Carlo simulation. The results showed that these compounds exhibited good inhibition efficiency, increasing in the order: Py II (84.9 %) < Py III (87.9 %) < Py I (90.1 %) at 10 mM. The pro¬tection efficiency improved with higher inhibitor concentration and decreased with rising temperature. Thermodynamic parameters for the inhibition process were calculated, with /delta)Hads0 values of -17.76±0.607, -15.8±0.101 and -16.24±0.118 kJ mol-1 for Py I, Py II and Py III, respectively, confirming the exothermic nature of adsorption. The adsorption fol¬lowed the Langmuir isotherm and occurred physically and spontaneously. Monte Carlo simulations indicated that PYs adsorbed in a parallel configuration, provide better cover¬age of the metal surface with high adsorption energy. SEM confirmed formation of a protective layer. Based on experimental and theoretical data, pyrazolone derivatives are recommended as corrosion inhibitors for copper in H2SO4 media.